Zero-Day Attack Detection in Industrial Control Systems Based on Siamese Neural Networks - Zając, Tadeusz; Sowa, Edmund (Journal of Applied Automation Technologies, 2024)
Industrial Control Systems are responsible for regulating the conditions in a particular area, and the reliability of this regulation depends on sensors, controllers, actuators and supervisory networks. Zero-day attacks are difficult to detect as they do not have known signatures and can maintain protocol validity by modifying process-state relationships. A Siamese Neural Network Framework for Zero-Day Attack Detection in Industrial Control Systems. Encode multi-source cyber-physical observations as paired process-state windows, map each window into a metric embedding space, and determine whether a suspicious window is close to the normal reference behaviour. To reduce false alarms and keep the sensitivity to unseen attacks, a safety-weighted contrastive objective, an adaptive open-set threshold and a temporal consistency filter are added. As shown in the example experimental data from an ICS testbed scenario, the proposed method has achieved 98.4% accuracy, 97.6% F1-score, 96.9% zero-day recall, and a false alarm rate of 1.8%, thereby surpassing the performance of autoencoder, one-class SVM, LSTM, CNN-LSTM and standard Siamese baselines. Ablation experiments show that the largest increase in performance for unknown attacks comes from safety-aware weighting and adaptive thresholding. A system for identifying new industrial attacks by means of similarity learning, rather than learning attack signatures.